COVID-19 Review: An Epidemiological Perspective and Malaysian Scenario in Handling the Pandemic (January - May 2020) / Zahir Izuan Azhar ... [et al.] - Azhar, Zahir Izuan; Chen, Xin Wee; Mohamad, Mariam; Ahmad Saman, Mohd Shahril; Isa, Mohamad Rodi; Ismail, Nurhuda (Universiti Teknologi MARA Cawangan Selangor, 2020)
The pandemic of Coronavirus Disease 2019 (COVID-19) has brought much fear and anxiety worldwide due to the rapid transmission rate and mortality. The exponential surge of COVID19 cases need to be addressed aggressively to flatten the epidemic curve. This review aims to describe the COVID-19 disease epidemiology and disease transmission, response actions taken by the authorities to control this pandemic and risk communication strategies in Malaysia. A literature search via the ScienceDirect and Google Scholar databases of published articles and official statements from the Ministry of Health, Malaysia from December 2019 to May 2020 was conducted. The first wave of COVID-19 outbreak in Malaysia started in late January involving 22 cases but the second wave involved more cases due to the massive religious gathering that occurred in late February. Malaysia implemented the Movement Control Order (MCO) on 18th March 2020 and other well-coordinated response action plans to prevent community transmission. The reproduction number (R0) was successfully reduced from 3.6 to 0.3 due to the MCO. Malaysia's risk communication strategies that include daily press conference by the Director General of Health and dissemination of information through national television and social media, played a crucial role in dealing with the COVID-19 outbreak. In conclusion, effective response actions and mitigation plans, should be the main priorities to combat this pandemic. The immediate direction will need to be focused on development of vaccines for COVID-19. Future research should study the origin of the virus in animals and the role of comorbidities contributing to poorer prognosis.